Campus Canopy, 1937-02-05 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1937)
Marionette Show, Critic of Art. Spanish Dancer are Billed -- Marriage Study Class Wants Men With Strong Character -- Five Nominations Made For S.G.A.
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals